2009
DOI: 10.1038/ismej.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transfer of the nitrogen fixation gene cluster in the cyanobacterium Microcoleus chthonoplastes

Abstract: The filamentous, non-heterocystous cyanobacterium Microcoleus chthonoplastes is a cosmopolitan organism, known to build microbial mats in a variety of different environments. Although most of these cyanobacterial mats are known for their capacity to fix dinitrogen, M. chthonoplastes has not been assigned as a diazotrophic organism. None of the strains that were correctly identified as M. chthonoplastes has been shown to fix dinitrogen and it has repeatedly been reported that these organisms lacked the cyanobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 38 publications
5
74
0
6
Order By: Relevance
“…The genes with the highest K values were nifI 1 /nifI 2 (K ϭ 4.18; P ϭ 0.001), nifW (K ϭ 1.36; P ϭ 0.001), and nifZ (K ϭ 1.26; P ϭ 0.001). These observations suggest a general trend of recruitment and vertical inheritance of nif genes, although gene loss (e.g., nifI 1 and nifI 2 ) and horizontal gene transfer events have also impacted the evolution of Nif (3,7,8,44).…”
Section: Resultsmentioning
confidence: 98%
“…The genes with the highest K values were nifI 1 /nifI 2 (K ϭ 4.18; P ϭ 0.001), nifW (K ϭ 1.36; P ϭ 0.001), and nifZ (K ϭ 1.26; P ϭ 0.001). These observations suggest a general trend of recruitment and vertical inheritance of nif genes, although gene loss (e.g., nifI 1 and nifI 2 ) and horizontal gene transfer events have also impacted the evolution of Nif (3,7,8,44).…”
Section: Resultsmentioning
confidence: 98%
“…Microcoleus chthonoplastes, the type strain for mat-dwelling Microcoleus spp., was for many years not thought to be a diazotrophic cyanobacterium. However, the recently completed genome of M. chthonoplastes PCC 7420 revealed a nif-gene cluster (Bolhuis et al, 2010) …”
Section: Discussionmentioning
confidence: 99%
“…NifH genes are present in a broad spectrum of prokaryotes, and the phylogenetic relationships among these organisms based on nifH sequences are largely congruent with those determined from 16S rRNA gene sequences (Zehr et al 2003b). This suggests that horizontal gene transfer of the nifH gene has been limited (Zehr et al 2003b), although it has been observed for several bacterial species (Raymond et al 2004, Kechris et al 2006, Bolhuis et al 2010. Consequently, nifH sequences are used to tentatively infer phylogenetic affiliations of diazotrophs in microbial communities.…”
Section: Nitrogenase Genes From Non-cyanobacteria Are Widespread In Mmentioning
confidence: 99%